Pendekatan Kualitatif Pengendalian Risiko Operasional pada Sistem Pembayaran Digital Usaha Kecil dan Menengah di Kabupaten Badung - Inggrid,T.M; Ni Nyoman Aryaningsih; I Made Bagiada (Jurnal Bisnis dan Kewirausahaan)
Society's dependence on digital technology emerged along with the development of digital technology. Digital technology has now innovated and one of the innovations is in the payment sector, namely the digital payment system. This digital payment system not only has many benefits but also has many risks, one of which is operational risk. This operational risk often occurs in MSMEs that receive digitalization encouragement by the government without adequate management to manage the operational risks of the digital payment system. This research aims to analyze the risk management process by identifying risks, assessing risks, classifying risk responses, and controlling operational risks of digital payment systems. The method used in this paper is a combination of qualitative and quantitative. A qualitative approach is used to identify risks and control operational risks of digital payment systems. A quantitative approach is used to assess risks and classify operational risks of digital payment systems. This research will be in accordance with the risk management process whose data will be obtained from informants and respondents. The results of this research are controls that can be implemented to anticipate losses caused by operational risks of digital payment systems for MSMEs. The implication of this research is that operational risk has a very important role for MSME businesses, so risks are designed to be anticipated at an early stage, for the sustainability of the MSME.